EMPLOYEE PLACEMENT EFFECT, KNOWLEDGE MANAGEMENT, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS INTERVENING VARIABLE (Research of the Jabodetabek Transportation Management Agency of the Ministry of Transportation) - Suryono Efendi; Galih Dwijayanda (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aims to analyze the effect of Employee Placement, Knowledge Management, Organizational Culture on employee performance with motivation as an intervening variable at the Jabodetabek Transportation Management Agency of the Ministry of Transportation. This research uses a survey method by distributing questionnaires to employees of the Jabodetabek Transportation Management Agency of the Ministry of Transportation as respondents. Quantitative research method with Structural Equation Modeling (SEM) analysis technique with AMOS version 24 application. The sample in this research were 150 respondents. The results of the research indicate that Employee Placement, Knowledge Management, Organizational Culture and Motivation have a direct positive and significant impact on employee performance at the BPTJ (Jakarta Transportation Management Body) of the Ministry of Transportation. Keywords: Employee Placement, Knowledge Management, Organizational Culture, Motivation, Employee Performance